Systems Approach to Human Hair Fibers: Interdependence Between Physical, Mechanical, Biochemical and Geometric Properties of Natural Healthy Hair - Cloete, Elsabe; Khumalo, Nonhlanhla P.; Van Wyk, Jennifer C.; Ngoepe, Malebogo N. (Frontiers in Physiology, 2019)
Contextual interpretation of hair fibre data is often blind to the effects of the dynamic complexity between different fibre properties. This intrinsic complexity requires systems thinking to decipher hair fibres accurately. Hair research, studied by various disciplines, follows a reductionist research approach, where elements of interest are studied from a local context with a certain amount of detachment from other elements or contexts. Following a systems approach, the authors are currently developing a cross-disciplinary taxonomy to provide a holistic view of fibre constituents and their interactions within large-scale dynamics. Based on the development process, this paper presents a review that explores the associated features, interrelationships and interactive complexities between physical, mechanical, biochemical and geometric features of natural, healthy hair fibres. Through the review, the importance of an appropriate taxonomy for interpreting hair fibre data across different disciplines is revealed. The review also demonstrates how seemingly unrelated fibre constituents are indeed interdependent and that these interdependencies may affect the behaviour of the fibre. Finally, the review highlights how a non-integrative approach may have a negative impact on the reliability of hair data interpretation.